THE POSITION OF MORAL VALUES IN LAW - Dian Latifiani; Raden Muhammad Arvy Ilyasa (Diponegoro Law Review, 2021)
Moral values in legal science are important. However, the flow of law sees a variety of moral values. This paper aims to see the position of moral values in the science of law. Legal positivism separates strictly between law and morals. According to him, there is no law other than the command of the authorities. Even extreme identifying the law (Recht) as the law (wet). Legal positivism activities are aimed at concrete problems, which are different when compared to natural law thinking which engages itself with the validation of man-made law. For adherents of natural law theory, an unjust law is not law. there is an absolute relationship between law and morality. the two cannot be separated, so the law must refer to moral principles.